Nilai Filosofis Dalam Upacara Bebantan Laman Pada Adat Dayak Tomun Lamandau - Budi Saputra (Syntax Idea)
This research aims to find out the philosophical meaning of the Berattan Laman ceremony in the Dayak Tomun tradition by using a field research method, which uses qualitative methods with a descriptive research nature. In this study, the aim is to preserve the rich culture of the Indonesian nation, the existence of which is starting to change along with the current development of globalization. The results of this research show that in the Dayak Tomun language, Berattan is an offering, while Laman is Kampung. There are five stages in carrying out the ceremony, namely Mantang Penggoro, Nangaian Nyasi, Pinyang/Prnyang, and sending off the Anca. The procedures are carried out on the 7th of the 7th month: fasting on Biya, washing heirlooms, setting rules for seating guests, and mentioning the terms of origin, family tree, Laman names, and cultural elements.